2008
DOI: 10.1007/s00018-007-7312-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mimicry in neurological disease: what is the evidence?

Abstract: Autoimmune diseases are a leading cause of disability and are increasing in incidence in industrialized countries. How people develop autoimmune diseases is not completely understood, but is related to an interaction between genetic background, environmental agents, autoantigens and the immune response. Molecular mimicry continues to be an important hypothesis that explains how an infection with an environmental agent results in autoimmune disease of the nervous system and other target organs. Although molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 123 publications
1
26
0
Order By: Relevance
“…Molecular mimicry is one mechanism that explains the association between an autoimmune response to an environmental agent acting as a contributor to the pathogenesis of MS. [87][88][89][90][91][92] The hypothesis of molecular mimicry describes the molecular consequences of immunological cross reactivity: when T-cells or antibodies specific for an environmental agent (such as a virus) cross react with a host antigen, resulting in target cell and organ damage. Previously it has been shown that patients with HTLV-1 Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP), an HTLV-1 virus induced spastic paraparesis clinically similar to MS, produce autoantibodies to the RNA binding protein hnRNP A1.…”
Section: Molecular Mimicrymentioning
confidence: 99%
See 4 more Smart Citations
“…Molecular mimicry is one mechanism that explains the association between an autoimmune response to an environmental agent acting as a contributor to the pathogenesis of MS. [87][88][89][90][91][92] The hypothesis of molecular mimicry describes the molecular consequences of immunological cross reactivity: when T-cells or antibodies specific for an environmental agent (such as a virus) cross react with a host antigen, resulting in target cell and organ damage. Previously it has been shown that patients with HTLV-1 Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP), an HTLV-1 virus induced spastic paraparesis clinically similar to MS, produce autoantibodies to the RNA binding protein hnRNP A1.…”
Section: Molecular Mimicrymentioning
confidence: 99%
“…[112][113][114] In addition, antibodies to hnRNP A1, B2 (hnRNP A1/B2) were present in CSF of MS and HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP) patients, but not in normal controls. 12,[92][93][94]97,98,115 hnRNPs are RNA-binding proteins that play a major role in adjustment of pre-mRNA splicing through various factors. 116 They also participate in mRNA stability, NF-k-ß dependent transcription and telomerase activity.…”
Section: Antibodiesmentioning
confidence: 99%
See 3 more Smart Citations